2012
DOI: 10.4236/jdm.2012.22028
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent relationship between serum metformin levels and glycemic control, insulin resistance and leptin levels in females newly diagnosed with type 2 diabetes mellitus

Abstract: Despite the extensive clinical experience with the use of metformin worldwide, no formal doseranging study has been conducted because the current dosing strategy of metformin was determined empirically, rather than by an understanding of its dose-response relationship in patients with type 2 diabetes. The present study was designed to evaluate the correlation between serum metformin levels and glycemic control, insulin resistance and leptin levels in females newly diagnosed with type 2 diabetes. Sixty type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This result was in agreement with Fadil et al, (2011) who reported that the use of metformin alone in diabetic males for 90 days have significantly decrease serum leptin levels by about 40.6%. Also, the treatment of diabetic females with different doses of metformin, significantly decreases the serum levels of leptin after 3 months treatment compared to baseline values (P < 0.05) (Kadhim et al, 2012).…”
Section: Mean ± Sd Groupsmentioning
confidence: 86%
“…This result was in agreement with Fadil et al, (2011) who reported that the use of metformin alone in diabetic males for 90 days have significantly decrease serum leptin levels by about 40.6%. Also, the treatment of diabetic females with different doses of metformin, significantly decreases the serum levels of leptin after 3 months treatment compared to baseline values (P < 0.05) (Kadhim et al, 2012).…”
Section: Mean ± Sd Groupsmentioning
confidence: 86%
“…Because metformin exists in its cationic form in the physiologic pH range, its passage across cell membranes is dependent on transporters, which determine its absorption, distribution, and elimination in various tissues. 14,15 The primary mediator of metformin uptake is the organic cation transporter OCT1, encoded by SLC22A1, which facilitates its cellular uptake. 16,17 In addition, metformin is transported by OCT2 from the circulation into the renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is currently the first-line drug for treatment of type 2 diabetes mellitus. Related studies have found that 4,5 it can effectively reduce blood sugar, lower insulin level, and increase insulin sensitivity with effects of anti-inflammatory, antioxidant stress, and anti-tumor. Relevant study has shown that 6 in type 2 diabetes patients treated with statins and metformin at the same time, the incidence of prostate cancer is significantly lower.…”
Section: Introductionmentioning
confidence: 99%